The Electronic Structure of Gax In 1-x As and InASx P1-x Using the Recursion Method - Mousa Al- Hasan (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The calculation of the electronic structure of Gax In 1-x As and In Asx P1-x alloys using the recursion method is reported. A five-orbitals, sp3s*, per atom model is used in the tight-binding representation of the Hamiltonian. The local density of states is calculated for Ca, In, As and P-sites in a cluster of 216 atoms. The results are in good agreement with other calculations.